Infiltrasi, sifat fisik tanah dan erosi pada berbagai lereng tangkapan mikro sub das kali babon Kabupaten Semarang=Infiltration, Soil Physical Properties and Erosion on Micro Catchment with Various Slope in Sub Kali ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
A research was done in Kedji, Ungaran District, Semarang Regency from November 2001 to April 2002, to study the infiltration rate, soil physical properties, and erosion rate of a small plot having different gradient scattered in microcatchment of sub Babon river watershed, Semarang Regency. Experimental design was Split Plot with three replicates, microcatchment of Tegalan and Rambutan as main plot, and slope: 15,25,40, and 60% as sub plot. Plot of 1 x 1 m2 size were made in levelled soil surface no tillage, on flat open spot free from gravels and shading from plant canopy or tree trunk in each respective designations. Soil texture, organic matter, soil aggregate stability, bulk density, permeability, pori distribution, and pH were taken from 0-10 cm soil depth were determined from samples. Rainfall, run off and soil loss were measured from daily rainfall. Volume of infiltration was calculated from effective rainfall minus run-off. Effective rainfall was calculated from rainfall ombro meter multiplied with slope degree. Infiltration capacity was measured using double ring infiltrometer method and calculated using Horton formula. Rainfall erosivity was determined using Bols and EI^ formula. Soil erodibility value was determined following USLE and using nomograph. The results indicated that higher slope degree affected reduce volume, rate, and capacity of infiltration, and increased run-off and soil loss. However, increase of run-off occurred following exponential graph. In Tegalan and Rambutan microcatchments open space with no vegetation, during rainy season there would be reduction of organic matter, soil permeability, rapid drainage pores, and water available pores accompanied with an increase of bulk density. In Tegalan microcatchment, run-off, soil loss, and erodibility were higher. On the oher hand, in Rambutan microcatchment, infiltration, organic matter, and soil aggregate stability were higher, resulting in a more stable condition to erosion. Result also found that predicted soil erodibility value using USLE formula was lower than nomograph.